An act for regulating the militia of this Commonwealth, 13 W.W. Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia Ch. 4 at 355 (Richmond, 1823) - (:unkn) unknown (My University, 1792)
"All arms, ammunition, and equipments of the militia, shall be exempted from executions and distresses at all times?"
Keywords: GUARANTEED RIGHT